Psycholinguistics of Virtual Communication in the Context of the Dependence on Social Networks - Olga Kaminska; Yuri Stezhko; Liudmyla Gliebova (Психолінгвістика)
The article deals with the problem of determining psychological peculiarities of virtual communication of people, who in a great degree are characterized by dependence on social networks. The author of the article has done a comparative analysis of the peculiarities of cyber-communication of addicts and other Internet users. There were analyzed gender differences of virtual communication. It was established that in the contemporary society virtual communication had become more widespread especially if to analyze it according to the latest information technologies. In such a way the process of interpersonal communication is gradually supplanted by virtual means of transmitting information. The specificity of virtual communication was especially emphasized when the person used social networks which served to maintain contacts, to find like-minded people, to express emotional states, including those ones which were considered unacceptable by the society. There were determined psycholinguistic features of virtual communication in the Internet environment: psycholinguistic presuppositions, psycholinguistic semantic presuppositions, pragmatic, psycho-linguistically marked presuppositions. It was underlined that psycholinguistic presupposition is a special kind of logical mastering of virtual information, cognitive explication of frames by means of actualization of a common fund of knowledge of participants in communication about the world, its organization, the place of a person in it and others. Also, in the Internet environment psycholinguistic semantic presuppositions often take place. Them we’ll analyze as a certain semantic component of the message (statement, judgment), the inaccuracy of which in a particular situation makes the message abnormal or inappropriate. It was emphasized that in the space of virtual communication, the pragmatic, psycho-linguistically marked presupposition, which are a component of the message, the speech genre, and discourse (or a text), are directly related to subjective factors of Internet communication (orientation in different situations of virtual communication, actualization of social, cognitive, gender, etc., characteristics of people in one communicative act), the absence of which converts a message, speech genre, discourse (or a text), virtual communication in general into inappropriate – such as insincere, unnatural, provocative, that do not conceal positive conditions, which make a success in a whole.